A Comprehensive Review of the Application of Zr-Based Metal–Organic Frameworks for Electrochemical Sensors and Biosensors - Tasca-Gottardo, F; Tasca-Gottardo, F (Springer, 2024)
A family of inorganic-organic hybrid crystalline materials made up of organic ligands and metal cations or clusters is known as metal-organic frameworks (MOFs). Because of their unique stability, intriguing characteristics, and structural diversity, zirconium-based MOFs (Zr-MOFs) are regarded as one of the most interesting families of MOF materials for real-world applications. Zr-MOFs that have the ligands, metal nodes, and guest molecules enclosed show distinct electrochemical reactions. They can successfully and sensitively identify a wide range of substances, which is important for both environmental preservation and human health. The rational design and synthesis of Zr-MOF electrochemical sensors and biosensors, as well as their applications in the detection of drugs, biomarkers, pesticides, food additives, hydrogen peroxide, and other materials, are the main topics of this comprehensive review. We also touch on the current issues and potential future paths for Zr-MOF electrochemical sensor research. Graphical abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2024.